Blm10 and PI31 comprise a failsafe mechanism for proteasome inhibition - Darlene Fung; Shaun Rawson; Richard M. Walsh; Erignacio Fermin Perez; Urte Venclovaite; Tamayanthi Rajakumar; Benjamin Velez; John Hanna (Proceedings of the National Academy of Sciences, 2026)
Blm10 (PA200 in mammals) is an evolutionarily conserved regulator of the proteasome’s core particle (CP), a barrel-shaped complex that houses six individual protease subunits. Despite decades of study, Blm10’s function has remained unresolved. Here, we provide structural, biochemical, and genetic evidence that yeast Blm10 inhibits the proteasome and that it does so in cooperation with a second proteasome inhibitor, PI31 (also known as Fub1). Both proteins are highly enriched in CPs with abnormal subunit composition, suggesting that Blm10 and PI31 may function to neutralize aberrant proteasomes. We report an unexpected proteasome configuration in which Blm10’s dome-like structure completely encases PI31’s N-terminal domain, which sits outside and atop the CP, while PI31’s C-terminal domain is present inside the CP, simultaneously inhibiting all six active sites. These Blm10/PI31-bound CP are strongly deficient in degradation of both proteins and small peptides, and loss of both proteins results in strongly synergistic genetic phenotypes in vivo. These data suggest that Blm10 and PI31 constitute a partially redundant failsafe system for proteasome inhibition.